Colostrum avoidance and associated factors among mothers of less than 6-month-old children in Dilla town, Southern Ethiopia - Gashaw, Anteneh; Kebede, Daniel; Regasa, Teferi; Bekele, Hermela (Frontiers in Pediatrics, 2024)
Background Colostrum, often referred to as “golden milk,” is the initial milk produced after birth, crucial for preventing childhood malnutrition and boosting natural immunity. Neglecting colostrum intake heightens vulnerability to infections and mortality, particularly in developing regions of the world. Colostrum avoidance is prevalent in Ethiopia. This research aims to investigate the frequency and factors that contribute to colostrum avoidance in Dilla town, Southern Ethiopia. Method A community-based, cross-sectional study was carried out in late 2023. Data were gathered from 350 participants, selected through multistage sampling, using structured questionnaires and face-to-face interviews. Data entry was conducted using Epi Data version 4.2.0 and transferred to Stata version 18 for analysis. Bivariate and multivariable logistic regression analyses were employed to identify the factors associated with colostrum avoidance, with a significance level of p < 0.05. Result The rate of prevalence of colostrum avoidance was 28.3% [95% confidence interval (CI): 18.4%–38.2%]. Late initiation of breastfeeding [adjusted odds ratios (AOR) 4.15, 95% CI: 2.51–6.84] prelacteal feeding, non-use of postnatal care (PNC) (AOR 1.79, 95% CI: 1.05–3.04), and lack of information about colostrum (AOR 1.88, 95% CI: 1.14–3.08) were the factors significantly associated with colostrum avoidance. Conclusions and recommendations A high prevalence of colostrum avoidance was observed, with prelacteal feeding, delayed initiation of breastfeeding, lack of PNC, and inadequate maternal knowledge about colostrum identified as contributing factors. Consequently, interventions aimed at reducing colostrum avoidance should prioritize improving access to and promotion of PNC, promoting timely initiation of breastfeeding, and intensifying awareness campaigns highlighting the advantages of colostrum, while emphasizing the risks associated with prelacteal feeding.